Awareness and Care Giving Attitudes of Medical Undergraduates towards Alzheimer’s Disease - A Cross Sectional Study - Hunniya Bint E Riaz, Qudsia Umaira Khan, Zainab Ahsan, Abdurehman Arshad, Lareb Hassan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Alzheimer’s disease is a severely debilitating disease that affects the number of elderly across the world. People especially the caregivers are bit reluctant to take care of such patients particularly because of the rapid progression of the disease and very little hopes of them to recover. Aim: To evaluate the awareness, approach and care giving attitude of medical students towards the patient suffering from Alzheimer’s disease. Methods: A cross sectional study was carried out on medical undergraduates in CMH LMC IOD. A questionnaire including demographic profile, 11 awareness and 11 attitude questions was fulfilled by 384 students. Results: Overall,>90% people knew he basic knowledge like primary symptoms, age of onset, genetic predisposition and role of gender in getting disease. About 75% students know about the treatment options, mortality rate and diagnostic techniques. Awareness score revealed that 85% of students had adequate information about Alzheimer’s disease. MBBS students and nursing Students had considerably enhanced understanding in contrast with other undergraduates. As far as attitude is concerned,>70% of students demonstrated positive attitudes amongst which the nursing students were on top. Conclusion: The undergraduates demonstrated better knowledge and positive attitude care giving skills attitudes towards patients of Alzheimer’s disease with a noticeable differentiation as far as various disciplines are concerned. Additional attempts are still needed to remove the stigma and hesitation concerned with such patients. Keywords Alzheimer’s disease, Elderly, Distress, and Stigma Knowledge